Going digital: Disruption and transformation in software‐intensive embedded systems ecosystems. Issue 6 (7th January 2020) - Olsson, Helena Holmström; Bosch, Jan
Abstract: Digitalization is transforming industry to an extent that we have only seen the beginnings of. Across domains, companies experience rapid changes to their existing practices due to new technologies and new entrants that current businesses. While digitalization brings endless opportunities, it comes with challenges that require companies to strategically engage with partners in their surrounding ecosystems. In this paper, we study how companies in the embedded systems domain experience the process of transitioning from product‐based companies to businesses where software, data, and artificial intelligence (AI) play an increasingly important role. To manage this, these companies need to evolve their existing ecosystems while at the same time create new ecosystems around new technologies. This involves maintaining existing technologies such as mechanics and electronics while at the same time expanding these with software, data, and AI. We provide a strategic decision framework that helps software‐intensive embedded systems companies to successfully navigate the digital transformation. We do this in two steps. First, we present three models that provide the technical content of the strategic decision framework. Second, we provide an overview of the strategic alternatives that incumbents and new entrants have available when existing technologies are commoditizing and new technologies are introduced. Abstract : The generally held opinion by the research community is that digitalization disrupts companies. However, very few people study how disruption happens in practice and how incumbents can avoid disruption and maintain their competitiveness. Based on six case study companies in the embedded systems domain, in this paper, we present a framework consisting of three models describing the dynamics between incumbents and new entrants during digital transformation of an industry.